Timing of prostaglandin F2α treatment in an estrogen-based protocol for timed artificial insemination or timed embryo transfer in lactating dairy cows - Pereira, M. H C [UNESP]; Sanches, C. P. [UNESP]; Guida, T. G. [UNESP]; Rodrigues, A. D P [UNESP]; Aragon, F. L.; Veras, M. B.; Borges, P. T.; Wiltbank, M. C.; Vasconcelos, José Luiz Moraes [UNESP] (American Dairy Science Association, 2013)
Objectives were to investigate progesterone concentrations and fertility comparing 2 different intervals from PGF2α treatment and induced ovulation in an estrogen-based ovulation synchronization protocol for timed artificial insemination (TAI) or timed embryo transfer (TET) in lactating dairy cows. A total of 1,058 lactating Holstein cows [primiparous (n=371) and multiparous (n=687)], yielding 34.1±0.33 kg of milk/d at various days in milk were randomly assigned to receive treatment with PGF2α on either d 7 or 8 of the following protocol: d 0: 2mg of estradiol benzoate + controlled internal drug release device; d 8: controlled internal drug release device removal + 1.0mg of estradiol cypionate; d 10: TAI or d 17: TET. Only cows with a corpus luteum at d 17 received an embryo and all cows received GnRH at TET. Pregnancy diagnoses were performed by detection (transrectal ultrasonography) of an embryo on d 28 or a fetus on d 60. Fertility [pregnancy per artificial insemination (P/AI) or pregnancy per embryo transfer (P/ET)] was affected by breeding technique (AI vs. ET) and time of PGF2α treatment (d 7 vs. 8) at the 28-d pregnancy diagnosis for TAI [32.9% (238) vs. 20.6% (168)] and TET cows [47% (243) vs. 40.7% (244)] and at the 60-d pregnancy diagnosis for TAI [30% (238) vs. 19.2% (168)] and TET cows [37.9% (243) vs. 33.5% (244)]. The progesterone (P4) concentration at d 10 altered fertility in TAI cows, with higher P/AI in cows with P4 concentration <0.1 ng/mL compared with cows with P4 concentration ≥0.1 ng/mL, and in ET cows, with higher P/ET in cows with P4 concentration <0.22 ng/mL compared with cows with P4 concentration ≥0.22 ng/mL. Prostaglandin F2α treatment at d 7 increased the percentage of cows with P4 <0.1 ng/mL on d 10 [39.4 (85) vs. 23.2 (54)]. Reducing the period between PGF2α and TAI from 72 to 48h in dairy cows resulted in a clear reduction in fertility in cows bred by TAI and a subtle negative effect in cows that received TET. The earlier PGF2α treatment benefits are most likely mediated through gamete transport, fertilization, or early embryo development and a more subtle effect of earlier PGF2α treatment that may be mediated through changes in the uterine or hormonal environment that manifests itself after ET on d 7. © 2013 American Dairy Science Association.
Keywords: Dairy cow; Fertility; Progesterone; Prostaglandin F2α; Bos